Grid Mapping the Northern Plains of Mars: Using Morphotype and Distribution of Ice‐Related Landforms to Understand Multiple Ice‐Rich Deposits in Utopia Planitia. Issue 2 (21st February 2019) - Séjourné, Antoine; Costard, Francois; Swirad, Zuzanna M.; Łosiak, Anna; Bouley, Sylvain; Smith, Isaac; Balme, Matthew R.; Orgel, Csilla; Ramsdale, Jason D.; Hauber, Ernst; Conway, Susan J.; van Gasselt, Stephan; et al.
Abstract: This work in Utopia Planitia is the first continuous regional mapping of ice‐related landforms integrated into an effort to study the three main basins (Arcadia, Acidalia, and Utopia Planitiae) in the northern plains. The distribution and morphotypes of these landforms, SHAllow RADar detections, and crater size‐frequency distribution measurements (>50 m in diameter) were used to understand the permafrost cryolithology and its past evolution in relation to climate in Utopia Planitia. Three assemblages of landforms were identified based on their spatial correlation and correlation with Mars Orbiter Laser Altimeter surface roughness along a strip from 30°N to 80°N. At 30°–38°N, the assemblage is formed by kilometer‐scale polygons, high‐albedo mounds, and thumbprint terrains. This assemblage is associated with a lobate deposit of 30 m in thickness with a crater retention age of 1 Ga. At 38°–47°N, the assemblage is comprised of large scallops, 100‐m‐diameter polygons, pits, and mantled deposits. This assemblage is correlated with a deposit of 80 m in thickness containing excess ice (~50–85% by volume) with a crater retention age of about 10 Ma. At 47°–78°N, the assemblage is composed of mantled deposits, textured terrains, and 30‐m‐diameter polygons. This assemblage is related to the ice‐rich, debris‐covered, latitude‐dependent mantle that has a crater retention age of about 1.5 Ma. Utopia Planitia appears to be a region of combined depositions of sediment and continuous cold climatic conditions that leaded to a complex distribution of ground ice. Plain Language Summary: The northern plains of Mars comprise several basins filled by sediments. The region has been proposed to have hosted an ancient ocean and currently contains ice in the ground even at latitudes where the ice is not stable. It is not known, however, what is the origin of the ice, whether it is related to the ancient ocean or recent glaciations. The ages of different surfaces and landforms are also not well known. Improving the geological context of the northern plains will help constrain outstanding questions about evolution of the climate and geology on Mars. An International Space Science Institute team project, composed of several European laboratories with expertise in mapping, has been convened to study targeted areas in the northern plain of Mars. In Utopia Planitia, we mapped and used the distribution of ice‐related landforms and radar sounding to understand the distribution of ice over the region. Two young ice‐rich deposits with different ice content were identified over the middle and high latitudes of the region. Similar to some regions in the Arctic on Earth, Utopia Planitia appears to be a region of combined deposition of sediment and continuous cold climatic conditions that partially preserved several ice‐rich deposits. Key Points: Distribution and morphotype of ice‐related landforms were used to understand the permafrost cryolithology and evolution in Utopia Planitia A midlatitude, ice‐rich, stratified permafrost (50–85% by volume) of 11‐Ma age occurs from 38°N to 47°N The latitude‐dependent mantle of about 1.5‐Ma age is present from 47°N to 78°N